The Ability of Proof Using Mathematics Induction Through Cooperative Learning Type Team Assisted Individualization - Wulan Izzatul Himmah (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
The ability to prove is one of the skills that need to be mastered by pre-service mathematics teachers. One method of proof in mathematics is using mathematical induction. However, from previous research, it is known that they still make common mistakes when proving using mathematical induction. This study aims to determine the difference in increasing the ability to prove using mathematical induction between pre-service teacher Mathematics Education program in IAIN Salatiga who study with cooperative learning type Team Assisted Individualization (TAI) and who receive conventional learning and to determine the size effect of the application of cooperative learning type TAI towards pre-service teachers’ ability to prove using mathematical induction. This research is a quasi-experimental study with a nonequivalent control group design. The population in this study were 107 pre-service mathematics teachers of the Mathematics Education Program of IAIN Salatiga who were taking the Set Logic course. Sampling used the purposive sampling technique and selected class A as the experimental class and class C as the control class. The instrument in this study used essay test questions. Data were analyzed using an independent sample t-test to determine the difference in the average N-Gain of the two sample groups. The results showed the difference in increasing the ability to prove using mathematical induction between a pre-service teacher who received learning through cooperative learning type TAI and a pre-service teacher who received conventional learning. In addition, the size effect of the application of cooperative learning type TAI toward the ability to prove using mathematical induction is categorized as medium. Keywords: Team Assisted Individualization, Mathematical Proof, Mathematical Induction.